Estudo paramétrico da segregação gravitacional na injeção contínua de vapor - Rodrigues, Marcos Allyson Felipe (2008)
Steam injection is the most used method of additional recovery for the extraction of heavy oil. In this type procedure is common to happen gravitational segregation and this phenomenon can affect the production of oil and therefore, it shoulds be considered in the projects of continuous steam injection. For many years, the gravitational segregation was not adequately considered in the calculation procedures in Reservoir Engineering. The effect of the gravity causes the segregation of fluids inside the porous media according to their densities. The results of simulation arising from reservoirs could provide the ability to deal with the gravity, and it became apparent that the effects of the gravity could significantly affect the performance of the reservoir. It know that the gravitational segregation can happen in almost every case where there is injection of light fluid, specially the steam, and occurs with greater intensity for viscous oil reservoirs. This work discusses the influence of some parameters of the rock-reservoir in segregation as viscosity, permeability, thickness, cover gas, porosity. From a model that shows the phenomenon with greater intensity, optimized some operational parameters as the rate flow rate steam, distance between the wells injector-producer, and interval of completion which contributed to the reduction in gravity override, thus increasing the oil recovery. It was shown a greater technical-economic viability for the model of distance between the wells 100 m. The analysis was performed using the simulator of CMG (Computer Modeling Group-Stars 2007.11, in which was observed by iterating between studied variables in heavy oil reservoirs with similar characteristics to Brazilian Northeast